Development of higher order thinking skill-based questions on students' creative thinking ability - Evi Fauziah; Mudmainah Vitasari; Lulu Tunjung Biru (Jurnal Pijar Mipa, 2021)
The study aims to develop valid higher-order thinking skill-based questions on the water and life topics for measuring junior high school students' creative thinking ability. The Borg and Gall development model was applied in this study. The development steps were limited to the fifth step, including identifying potential and problems, collecting data, designing the product, validating the design, and revising the design. The instrument used is a logical validation questionnaire that utilizes a Likert scale to ascertain the validity of the questions based on expert judgment and their reliability scores. The development of higher-order thinking skill-based questions on Junior High School students shows that the developed product is valid. It is based on expert validity assessments conducted by material, evaluation, and educator experts. A total of 27 questions were tested, and the average validity score of 77%, 80%, and 84% from the material, evaluation, educator expert assessments, respectively. ÃÂ In conclusion, all 27 questions developed are valid, with an overall average validation score of 80% and a reliability score of 83.7% in the very reliable category.